Evaluation of integrated crop management strategies employed to cope with Striga infestation in permanent land use systems in southern Benin - VISSOH, VINASSÉHO PIERRE; GBEHOUNOU, GUALBERT; AHANCHEDE, ADAM; RÖLING, Niels; KUYPER, THOMAS W. (My University, 2008)
Striga hermonthica and S. gesnerioides pose serious threats to cereal and cowpea production, endangering peoples' livelihoods on the Abomey plateau, Benin. A 2-year joint experiment was undertaken with farmers in two hamlets to investigate the potential of managing sowing dates of cowpea, sorghum transplanting, and trap cropping as ways of increasing agricultural production and reducing Striga damage. Early sowing of cowpea failed due to dry spells. Late sowing reduced cowpea yield due to water deficiency at the end of the growing season. Transplanting sorghum seedlings raised in fertilised or Striga-free nurseries doubled or tripled cereal yield and substantially reduced S. hermonthica infestation compared to direct early-sown sorghum. Transplanting sorghum from plant hills to fill gaps was unsuccessful. Trap crops such as cowpea and groundnut increased subsequent maize yield. Trap cropping had only a small effect on S. hermonthica infestation. The very poor soils in Som central were a major constraint upon yield improvement to acceptable levels even after the introduction of the new crop (and Striga) management methods
Keywords: Soil fertility decline; Striga; crop losses; participatory learning; integrated crop management; permanent land use; transplanting; legumes